Upaya Kh. Ahmad Shiddiq Dalam Mengembalikan Nahdhatul Ulama Pada Khittah Awal (1926) Tahun 1984 - nasrul nasrul; zaenal abidin; erdi rujikartawi (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2018)
The implementation of the 27th Nahdhatul Ulama in Situbondo in 1984 was caused by several factors. Among them is the reduction in votes which resulted in the NU Party's seats in the Parliament by the policy of H. Jaelani Naro as General Chair of the United Development Party (PPP). Secondly, the conflict that occurred within the NU was between senior kiyai (Syuriyah NU) and the Nahdhatul Ulama Politicians (Tanfidziyah NU) in Jakarta. The chaplain considers that the NU politicians in making decisions on party problems without considering deliberating with the chaplain. In addition, the NU Politicians only pursued their own personal interests not for NU's progress. So the Kiyai had a strategy for NU to return to Khittah (1926) in 1984. The formulation of the problem in this thesis is as follows: How is biography of KH Ahmad Shiddiq?, What was the Condition of the Nahdhatul Ulama Before Returning to the Khittah in 1984? How was the Role of KH. Ahmad Shiddiq in the Return of Nahdhatul Ulama to the Khittah in 1984? The aim of this reseach is to finding out: How is history life of KH Ahmad Siddiq, What is the condition of the Nahdhatul Ulama Before Returning to the Khittah in 1984, What is the Role of KH. Ahmad Shiddiq in the return of the Nahdhatul Ulama to the Khittah 1984 became the focal point in this study. The method used in this study is the Historical Research Method which consists of several stages, namely selection of topics, heuristics (data collection), criticism, interpretation, and historiography.